Acute migraine therapy with external trigeminal neurostimulation (ACME): A randomized controlled trial. (January 2019) - Chou, Denise E; Shnayderman Yugrakh, Marianna; Winegarner, Dana; Rowe, Vernon; Kuruvilla, Deena; Schoenen, Jean
Objective: To assess the safety and efficacy of external trigeminal nerve stimulation for acute pain relief during migraine attacks with or without aura via a sham-controlled trial. Methods: This was a double-blind, randomized, sham-controlled study conducted across three headache centers in the United States. Adult patients who were experiencing an acute migraine attack with or without aura were recruited on site and randomly assigned 1:1 to receive either verum or sham external trigeminal nerve stimulation treatment (CEFALY Technology) for 1 hour. Pain intensity was scored using a visual analogue scale (0 = no pain to 10 = maximum pain). The primary outcome measure was the mean change in pain intensity at 1 hour compared to baseline. Results: A total of 109 participants were screened between February 1, 2016 and March 31, 2017. Of these, 106 patients were randomized and included in the intention-to-treat analysis (verum: n = 52; sham: n = 54). The primary outcome measure was significantly more reduced in the verum group than in the sham group: −3.46 ± 2.32 versus −1.78 ± 1.89 ( p < 0.0001), or −59% versus −30% ( p < 0.0001). With regards to migraine subgroups, there was a significant difference in pain reduction between verum and sham for 'migraine without aura' attacks: mean visual analogue scale reduction at 1 hour was −3.3 ± 2.4 for the verum group versus −1.7 ± 1.9 for the sham group ( p = 0.0006). For 'migraine with aura' attacks, pain reduction was numerically greater for verum versus sham, but did not reach significance: mean visual analogue scale reduction at 1 hour was −4.3 ± 1.8 for the verum group versus −2.6 ± 1.9 for the sham group ( p = 0.060). No serious adverse events were reported and five minor adverse events occurred in the verum group. Conclusion: One-hour treatment with external trigeminal nerve stimulation resulted in significant headache pain relief compared to sham stimulation and was well tolerated, suggesting it may be a safe and effective acute treatment for migraine attacks. Study protocol: ClinicalTrials.gov Identifier: NCT02590939.